Teachers must reclaim their authority in age of AI - Moris, Megawati (The Star Media Group, 2025)
This article reflects on the evolving challenges faced by educators in the age of generative artificial intelligence (AI). Drawing from semester-long observations, the author highlights how AI has altered students’ approaches to academic tasks, often resulting in overreliance, weakened critical engagement, and blurred authorship. While acknowledging AI’s benefits in efficiency and idea generation, the article argues that its integration into education requires thoughtful ethical frameworks and a renewed emphasis on Natural Intelligence (NI)—critical reasoning, moral discernment, and spiritual consciousness. The author contends that teachers must reclaim their authoritative role as mentors and moral guides, ensuring that human wisdom anchors learning processes amid rapid technological change. Ultimately, the article calls for collaborative efforts among educators, curriculum designers, and policymakers to develop balanced, responsible, and human-centred pedagogical practices in an AI-driven world.